Improving the state-tracking ability of corona dashboards. Issue 5 (3rd September 2021) - Recker, Jan
ABSTRACT: Corona dashboards are interactive geospatial information systems used by billions of users to help them understand the evolution of the COVID-19 pandemic. I use a representational lens to explore how these systems can be made more useful. With this lens, the usefulness of these systems to convey information about the pandemic fundamentally depends on whether these systems are implemented as representation or state-tracking systems. I suggest that corona dashboards presently focus disproportionally on representing socially constructed properties (infection rates, deaths, levels of vaccination) of various things such as people, regions, or countries. They would become more useful if they additionally focused on tracking events (such as policy implementations) and changes in states (such as capacities of lockdown wards, usage of face masks). By applying a methodology for design science research involving design archaeology, I analyse the in situ implementation of Germany's RKI COVID-19-Dashboard, develop new design principles to extend the state-tracking abilities of corona dashboards, and explore the importance, actability, and effectiveness of these design principles through an empirical case study. The contributions this paper makes are new and validated design principles for new feature implementations that can help making corona dashboards more effective and useful.